Neįgaliųjų integravimas į darbo rinką informacinės visuomenės sąlygomis - Petrauskas, Rimantas; Bilevičienė, Tatjana (Information & Media, 2008)
2000 metais Europos Tarybos patvirtinta Lisabonos strategija iškėlė tikslą per dešimtmetį Europos Sąjungą (ES) paversti dinamiškiausia žinių pagrindu augančia ekonomika pasaulyje, kartu didinant įdarbinimo galimybes ir socialinę sanglaudą. Ypatingas dėmesys turi būti skiriamas socialiai nuskriaustųjų, įskaitant neįgaliuosius, užimtumo skirtumams. Lietuva kartu su kitomis ES valstybėmis įsipareigojo daugiau rūpintis socialiai pažeidžiamiausiais asmenimis, plėtoti lanksčias ir neįgaliemsžmonėms labiau prieinamas darbo organizavimo formas. Jungtinių Tautų Neįgaliųjų teisių konvencija įtvirtina naują požiūrį į negalią turinčius žmones, pabrėžia jų teisę užsidirbti pragyvenimui iš laisvai pasirinkto darbo, verslumo ir nuosavo verslo. Verslo ir darbo rinka nėra palanki tokiems žmonėms, tačiau jiems gali padėti teledarbas ir e. verslas. Viena iš svarbių prielaidų neįgaliųjų atskirčiai mažinti yra interneto informacinės aplinkos pritaikymas šiems žmonėms. Straipsnyje aptariama galimybėįtraukti neįgaliuosius į darbo rinką, taikant naujas informacines technologijas.Integration of disabled to labour market according conditions of information societyRimantas Petrauskas, Tatjana BilevičienėSummaryLisbon Strategy stated new strategical aim for European Union – during decade to transform the European Union to most dynamic economic in the world, which asserting of increase and betterment of opportunities of employment, bigger social cohesion. While realising Lisbon Strategy it is concentrated to two main tasks – to encourage stronger permanent increase of economic and to create more and better place of work. The most important attention should be paid to differences between social disadvantaged, both to disabled. It is important to fight against discrimination, to encourage opportunities of disabled for employment. Lithuania successfully participates in realisation programmes of Lisbon Strategy. State undertook for every resident who would like and can work, to create opportunities to ensure proper level of life by his or her work, more to care of most socially vulnerable persons, to develop the flexible forms of work organisation. Development of information society is one of the three main priorities of Lithuanian Republic, stated in Lithuanian long development strategy. It fits the goals of European Union. Objectives of Lithuanian information society development are coordinated with attitudes and demands of Lisbon Strategy and initiative “eEurope – information society for everyone”. Disabled can integrate to labour market by taking part in distant work and e. business. It is quite important that disabled persons could use IT opportunities. Authors consider the opportunity of disabled integration in labour market by implementing modern information technologies.